Moderate altitude but not additional endurance training increases markers of oxidative stress in exhaled breath condensate - Heinicke, I.; Boehler, A.; Rechsteiner, T.; Bogdanova, A.; Jelkmann, W.; Hofer, M.; Rawlings, P.; Araneda, O. F.; Behn, C.; Gassmann, M.; Heinicke, K. (European Journal of Applied Physiology, 2009)
Oxidative stress occurs at altitude, and physical exertion might enhance this stress. In the present study, we investigated the combined effects of exercise and moderate altitude on redox balance in ten endurance exercising biathletes, and five sedentary volunteers during a 6-week-stay at 2,800 m. As a marker for oxidative stress, hydrogen peroxide (H2O2) was analyzed by the biosensor measuring system Ecocheck™, and 8-iso prostaglandin F2a (8-iso PGF2a) was determined by enzyme immunoassay in exhaled breath condensate (EBC). To determine the whole blood antioxidative capacity, we measured reduced glutathione (GSH) enzymatically using Ellman`s reagent. Exercising athletes and sedentary volunteers showed increased levels of oxidative markers at moderate altitude, contrary to our expectations; there was no difference between both groups. Therefore, all subjects` data were pooled to examine the oxidative stress response exclusively due to altitude exposure. H2O2 levels increased at altitude and remained elevated for 3 days after returning to sea level (p = 0.05). On the other hand, 8-iso PGF2a levels showed a tendency to increase at altitude, but declined immediately after returning to sea level (p = 0.001). Hypoxic exposure during the first day at altitude resulted in elevated GSH levels (p = 0.05), that decreased during prolonged sojourn at altitude (p = 0.001). In conclusion, a stay at moderate altitude for up to 6 weeks increases markers of oxidative stress in EBC independent of additional endurance training. Notably, this oxidative stress is still detectable 3 days upon return to sea level.